Effect of Non-Thermal Plasma on Biochar Properties from Sugarcane Bagasse and Banana Peel - Dermawan, Denny; Satriavi, Aulia Diva; Nurhidayati, Dyah Isna; Mujiyanti, Dwi Rasy; Novitrie, Nora Amelia; Mayangsari, Novi Eka; Setiawan, Adhi (Universitas Diponegoro, 2025)
Biochar produced from agricultural waste, such as sugarcane bagasse and banana peel, has gained significant attention owing to its potential environmental and industrial applications. This study aimed to enhance the physicochemical properties of biochar derived from these wastes using nonthermal plasma treatment. Biochar was produced via pyrolysis combined with non-thermal plasma treatment and then characterized to identify the differences. Characterization was performed using X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM), Fourier-transform infrared spectroscopy (FTIR), and–Brunauer–Emmett Teller (Brunauer-Emmett-Teller) surface area analysis to evaluate changes in crystallinity, morphology, functional groups, and surface area. Nonthermal plasma treatment significantly altered the surface morphology of biochar, increasing its porosity and surface area. The BET surface area of sugarcane bagasse waste was 0.061 m²/g, which expanded to 87.50 m²/g after changing to biochar, whereas banana peel waste had a BET surface area of 0.007 m²/g, which increased to 427.2 m²/g after changed to biochar. The pyrolysis process on both biochars also reduced OH (hydroxyl) transmittance, as evidenced by FTIR analysis, which indicated water evaporation. Non-thermal plasma treatment substantially improved the physical and chemical properties of biochar compared to untreated biomass.